Heat-Killed and Live Enterococcus faecalis Attenuates Enlarged Prostate in an Animal Model of Benign Prostatic Hyperplasia - Choi, Young-Jin; Fan, Meiqi; Tang, Yujiao; Iwasa, Masahiro; Han, Kwon-Il; Lee, Hongchan; Hwang, Ji-Young; Lee, Bokyung; Kim, Eun-Kyung (Journal of microbiology and biotechnology, 2021)
In the present study, we investigated the inhibitory effect of heat-killed ( ) and live on benign prostatic hyperplasia (BPH). The BPH rat model was established by administering male rats with testosterone propionate (TP, 5 mg/kg, in corn oil) via subcutaneous injections daily for four weeks after castration. The rats were divided into five groups: Con, corn oil-injected (s.c.) + DW administration; BPH, TP (5 mg/kg, s.c.) + DW administration; BPH+K_EF, TP (5 mg/kg, s.c.) + heat-killed (7.5 × 10 CFU/g, 2.21 mg/kg) administration; BPH+L_EF, TP (5 mg/kg, s.c.) + live (1 × 10 CFU/g, 166 mg/kg) administration; BPH+Fi, TP (5 mg/kg, s.c.) + finasteride (1 mg/kg) administration. In both of BPH+K_EF and BPH+L_EF groups, the prostate weight decreased and histological changes due to TP treatment recovered to the level of the Con group. Both of these groups also showed regulation of androgen-signaling factors, growth factors, and apoptosis-related factors in prostate tissue. exhibited an inhibitory effect on benign prostatic hyperplasia, and even heat-killed showed similar efficacy on the live cells in the BPH rat model. As the first investigation into the effect of heat-killed and live on BPH, our study suggests that heat-killed might be a food additive candidate for use in various foods, regardless of heat processing.